Peat Restoration Based On Islamic Education (Case Study in Banjarmasin, South Kalimantan) - Suhardin, Suhardin (AR-RASYID : Jurnal Pendidikan Agama Islam, 2024)
The objective research; first, factual exploration related to peat problems and restoration concepts in the context of ecosystem recovery and sustainability. Second, Islamic educational perspective, strategic opportunities for the community in maintaining sustainability. And third, social participation based Islamic Education, involving the community in making peat restoration a success in Banjarmasin, South Kalimantan. The method used is a case study, comprehensively describing the activities developed in Banjarmasin in order to package concepts, strategies, methodologies, steps and sustainable programs by involving the community to actively participate in the form of a movement to maintain the sustainability of the peat ecosystem. The findings of peat as biodiversity, hydrological, carbon sink, and minimize carbon emissions need to be understood and made aware both personally and in the community in the form of an integrated and sustainable movement. From these findings, it can be concluded that community participation is the key to the success of the program developed by the government and effective community participation by taking an Islamic education approach for the Muslim community.